Report of the radionuclides in nephrourology - Blaufox, Morton Donlad; Aurell, Mattias; Bubeck, Bernd; Fommei, Enza; Piepsz, Amnon; Russell, Charles; Taylor, Andrew; Thomsen, Henrik S.; Volterrani, Duccio (Journal of nuclear medicine, 1996)
The need for simple and accurate methods to measure renal function is self-evident. This need increases as techniques for intervention become available. The demand for evaluation of individual kidney function has increased with its role in the diagnosis and follow-up of unilateral renal disease and in decision making for conservative or surgical treatment based on residual renal function. The role of nuclear medicine in this area has been inhibited by confusion about conflicting methodologies. This report is meant to provide guidance to those centers that would like to initiate clearance procedures but have difficulty in choosing appropriate methodology.
Gesehen am 01.07.2024